Incidence of Parkinson disease and parkinsonism in three elderly populations of central Spain - Benito-León, J; Bermejo-Pareja, F; Morales-González, J M; Porta-Etessam, J; Trincado, R; Vega, S; Louis, E D (Neurology, 2004)
A two-phase investigation method (screening followed by detailed examination) is the most accurate epidemiologic approach to estimate the epidemiology of Parkinson disease (PD) and secondary parkinsonism. The scarcity of statistics on the incidence of PD and other types of parkinsonism using this methodology led the authors to estimate them in three elderly populations. A Spanish elderly parkinsonism-free cohort was followed for an average of 3 years. At the end of the follow-up, the cohort survivors were contacted by way of screening and clinical examination. The cohort consisted of 5,160 subjects (ages 65 to 85 and over): Eight hundred twenty-eight died before the examination, 3,685 completed the screening procedure, and 647 could not be screened because they refused (108) or were unreachable (539). Sixty-eight incident cases of parkinsonism were found: 30 PD (44.1%), 22 drug-induced parkinsonism (32.3%), 8 parkinsonism with associated features (11.7%), and 3 vascular parkinsonism (4.4%). The remaining five cases (7.3%) were classified as unspecified parkinsonism. Average annual incidence rate (per 100,000 person-years) in the population aged 65 to 85 and over years, adjusted to the standard European population, was 409.9 (95% CI 299.0 to 520.8) for parkinsonism and 186.8 (95% CI 110.4 to 263.2) for PD. Incidence rates of parkinsonism increased with advancing age. For PD, incidence rates increased with age in men but decreased beyond the age of 79 in women. Age-adjusted relative risk in men compared with women was 1.56 (95% CI 0.97 to 2.51) for parkinsonism and 2.55 (95% CI 1.21 to 5.37) for PD. Sixteen (53.3%) patients with PD were detected through the screening and had not been diagnosed previously. Incidence estimates of PD based on two-phase investigation methodology are higher than those based on other approaches. Men had a risk of developing PD that was twice that of women. A large proportion of PD patients may never seek neurologic attention.